Proposed Hiding Text in Text Based On RNA for Encoding Secret Information - Kadhem , Suhad M.; Ali , Dhurgham W. Mohammed (Iraqi Journal of Science, 2022)
In any security system, we need a high level of security, to maintain the secrecy of important data. Steganography is one of the security systems that are hiding secret information within a certain cover (video, image, sound, text), so that the adversary does not suspect the existence of such confidential information. In our proposed work will hide secret messages (Arabic or English) text in the Arabic cover text, we employed the RNA as a tool for encoding the secret information and used non-printed characters to hide these codes. Each character (English or Arabic) is represented by using only six bits based on secret tables this operation has provided a good compression since each Arabic character needs 16 bits and each English character needs 8 bits in a conventional method, using RNA with secret table has provided a good degree of security, moreover using non-printed characters, these characters do not appear on screen so have provided a complete similarity between the Arabic cover text and stegotext.